Linguistic Landscape Mapping as Identity Representation in Higher Education Institution - Ardhan, Dhea Tisane; Khoirunnisa, Ratna; Khairas, Eri Ester (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Not only functioning to demonstrate the importance of language use in public space, linguistic landscapes can also represent an institution’s identity. Taking an example of a higher education institution, linguistic landscapes can have the objective to establish the language regulation applied and also embody the identity or ideology of the higher education institution itself. This research is a continuation from the previous research which analyzes the bilingual linguistic landscapes found in vocational campus in Indonesia. However, the objective of this research is to explore more about the linguistic landscape mapping in a bigger context, which identifies the monolingual, bilingual, and multilingual types in one of vocational campus in Indonesia along with their information function. This research used a qualitative approach. The results show that only monolingual and bilingual types are found, but a multilingual linguistic landscape is not found. The monolingual linguistic landscapes are built using Indonesian language and English language. Furthermore, the bilingual linguistic landscapes are built using the combination of Indonesian, English, Arabic, and Chinese languages. The information functions of the linguistic landscapes found range from being the place or location marker until informing the institution’s slogan. In conclusion, the linguistic landscapes found in the campus area determine this institution’s identity which is aiming for an international acknowledgement while at the same time still prioritizing its nationalism value.